Implementation of Learning to Understand Narrative Text Information Using Teaching Materials Based on Local Wisdom Assisted by AKM-Class Instrument - Ilfa Munazah; Panca Dewi Purwati (KEMBARA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2025)
Education plays a crucial role in shaping the nation future, especially in the literacy and numeracy skills development among elementary school students. The impact of the COVID-19 pandemic on education is the occurrence of learning loss and the decline in the quality of students' literacy skills. Online learning causes learners to lack opportunities to interact with reading materials and practice their literacy skills effectively. This study aims to describe the design, implementation, and effectiveness of learning to understand narrative text information through local wisdom-based teaching materials assisted by a Classroom Minimum Competency Assessment (AKM) instrument at SD Negeri 2 Banglarangan. The mixed method (qualitative and quantitative) with the sequential exploratory model involves observation, interviews, and quantitative data analysis through tests. The results showed that the learning design used teaching materials based on the local wisdom of Widuri Beach with the Cooperative Integrated Reading and Composition (CIRC) model and the Class AKM assessment instrument. Learning can create an active and interactive learning atmosphere through group discussions. The effectiveness of learning can be seen from the improvement of students' post-test results with an increase in the average score of 22.5% from 66 to 88.5, as well as an increase in students' critical reasoning attitudes and independence. In conclusion, the integration of local wisdom in learning through the CIRC model with the Class AKM instrument effectively improves the ability to understand narrative text information, creates contextual and meaningful learning, and develops critical reasoning attitudes and independence of fourth-grade students of SD Negeri 2 Banglarangan, Ampelgading District, Pemalang Regency.